Enjeux d’une recherche collaborative : les présupposés épistémologiques et méthodologiques requis dans une analyse des processus de traduction - Christiane Montandon (Recherches en Éducation)
This synthesis aims to bring out from these nine articles the methodological presuppositions specific to the theorical framework of translation sociology. Examining the epistemological requisites invites to reject all positivism in favor of the involvement of the researcher: this posture assigns to those who present themselves as the research objects to also be subjects participating in the transactions carried out by all the actors engaged in a problematization process. The multidimensional nature of the field raises the question of steering the several stages of negotiation where uncertainty and heterogeneity require the support of different statutory groups and the recognition of established leadership. Such intervention research aims to bring about structural transformations within the institutions with the actors, who are gradually becoming a collective researcher; a critical look at this research allows us to identify the need to use intermediary spaces to facilitate these transitions and multiply mediations. One of the important blind spots concerns the heuristic analyzes restitution to be communicated to field’s actors, which can confirm this collaborative approach.